Development of an Entrepreneurship Themed Animation Film of Kappaphycus Striatum Integrated Linear Programming Using the Plotagon Application - Amsidi, Mukmin; Andriyani, Andriyani (Universitas Ahmad Dahlan, 2024)
Entrepreneurship is the answer to the challenge of the need for creativity and innovation in solving problems or creating new opportunities, as applied in vocational-based curricula. Various vocational competencies and skills are trained to equip and prepare students to enter the dynamic world of work so that students can solve problems encountered around them through creative problem-solving. Therefore, in its teaching, real problem-solving exercises are needed with the help of learning media that can illustrate these real problems in detail with very realistic visuals. Thus, this study aims to develop a valid, practical, and effective animated film to visualize realistic problems of entrepreneurial practice to improve students' creative thinking skills. The research and development model used in this research is the descriptive ADDIE model, which shows systematic steps to produce an animated film with an entrepreneurship theme. The basis for selecting this development model is related to the special characteristics of the ADDIE model, namely developing products to relate the gap between educational research and educational practice, as well as emphasizing specific problems related to practical problems in teaching through applied research. Animated films with the theme of entrepreneurial practices can meet the criteria for product development feasibility in terms of validity, practicality, and effectiveness. The animated film media used has also proven to be a solution to the problems of students who have not been trained to think creatively in solving entrepreneurial practice problems so that students are more enthusiastic about learning and have meaningful learning experiences.